2010
DOI: 10.1007/s10681-010-0234-8
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to the South American tomato pinworm Tuta absoluta in high acylsugar and/or high zingiberene tomato genotypes

Abstract: Zingiberene (ZGB) and acylsugars (AS) are allelochemicals responsible for high levels of arthropod resistance found in Solanum habrochaites (= Lycopersicon hirsutum) var. hirsutum 'PI 127826' and S. (= L.) pennelli 'LA 716', respectively. These accessions were used to develop commercial lines with good levels of pest resistance. The objective of the present work was to assess the ZGB and AS contents and the levels of resistance to Tuta absoluta in tomato hybrids between high ZGB 9 high AS lines, as compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 13 publications
(21 reference statements)
2
44
0
Order By: Relevance
“…These results are in accordance with that found by Azevedo et al (2003); Maluf et al (2007Maluf et al ( , 2010, Oliveira et al (2012) and Neiva et al (2013) who verified that high ZGB contents, together with high density of glandular trichomes, promote resistance of plants to spider mite, whitefly and tomato leafminer. According to Gonçalves et al (2006), high ZGB content is directly linked to high density of glandular trichomes.…”
Section: Resultssupporting
confidence: 91%
“…These results are in accordance with that found by Azevedo et al (2003); Maluf et al (2007Maluf et al ( , 2010, Oliveira et al (2012) and Neiva et al (2013) who verified that high ZGB contents, together with high density of glandular trichomes, promote resistance of plants to spider mite, whitefly and tomato leafminer. According to Gonçalves et al (2006), high ZGB content is directly linked to high density of glandular trichomes.…”
Section: Resultssupporting
confidence: 91%
“…Although all the leaves of all seven tomato cultivars were infested by T. absoluta larvae, only "Petomech," "Cal JN3," "Rio Grande" and "Early Urbana Y" cultivars had significant yield loss in both years. This could be due to the morphological or biochemical characteristics of each tomato cultivar (Azevedo, Faria, Maluf, Oliveira, & Freitas, 2003;Maluf, Silva, & Cardosa, 2010). Oliveira, Júnior, Maluf, Neiva, and Maciel (2012) demonstrated that genotypes associated with high densities of glandular trichomes were less favourable to T. absoluta, but whether that was the case with these cultivars remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we investigated life history and life table parameters of T. absoluta on these cultivars (Nouri-Ganbalani et al 2016). For example, at least three types of secondary metabolites, namely acyl sugars, zingiberene, and 2-tridecanone, are known in association with tomato resistance to T. absoluta (Maluf et al 2010;de Oliveira et al 2012). In line with these results, many studies have reported that the life parameters of and damage caused by T. absoluta vary significantly when the pest is reared on different tomato cultivars, and that these variations may arise from differences in the quality and quantity of nutrients, phagostimulant factors, trichome density, and the abundance of secondary metabolites among cultivars (Pereyra & Sanchez 2006;Proffit et al 2011;de Oliveira et al 2012;Sohrabi et al 2016b;Ghaderi et al 2017).…”
Section: Discussionmentioning
confidence: 99%